THE EFFECT OF PLUS MINUS INTERESTING ( PMI ) METHOD ON STUDENTS ACHIEVEMENT ON WRITING ANALYTICAL EXPOSITION ( A STUDY AT THE ELEVENTH GRADE OF STUDENS SMK NEGERI 1 PADANGSIDIMPUAN - S.Pd., M.Hum, ASRIANI HASIBUAN (Institut Pendidikan Tapanuli Selatan, 2017)
The purposes of this research is to find out whether there is away significant effect of plusminus interesting method on studentsâ achievement in writing analytical exposition text at theeleventh grade of students SMK Negeri 1 Padangsidimpuan. This research was conducted by usingexperimental method is one group pretest-posttest design.The population of this research is all of theeleventh grade students technique computer of SMK Negeri 1 Padangsidimpuan that consist of 71students. Then, the sample was taken from the population by cluster sampling technique, thetechnique for collecting data is by observation sheet and giving essay test and the total sample is 34students.After calculating the data experiment analysis, it was found that the mean score of studentswriting analytical exposition before taught by using plus minus interesting method is 60,75, it iscategorized âFairâ, while the mean score of students writing analytical exposition after taught byusing plus minus interesting method is 80, it is categorized âExcellentâ.The alternative hypothesiscan be accepted. Wherre the result of hyphotesis test shows that t test is 10,83, while the samples are34 students or N = 34 students. The degree of freedom (df) is N- 1 =34-1 = 33. The score df of t tableat 5% significant level from 33 is 2,03. So, from the based on the explanation above t test is higherthan t table (t test > t table= 10,83 > 2,03). It can be concluded that is a significant effect of PMI Methodon studentsâ achievement in writing analytical exposition text at the eleventh grade of SMK Negeri1 Padangsidimpuan.